Acerola: importance, culture conditions, production and biochemical aspects - de Assis, Sandra Aparecida [UNESP]; Fernandes, Fernandes Pedro; Geraldo Martins, Antonio Baldo [UNESP]; Mascarenhas de Faria Oliveira, Olga Maria [UNESP] (Cambridge University Press, 2008)
Origin and importance. Acerola, or Malpighia emarginata D. C., is native to the Caribbean islands, Central America and the Amazonian region. More recently, it has been introduced in subtropical areas (Asia, India and South America). The vitamin C produced by acerola is better absorbed by the human organism than synthetic ascorbic acid. Exportation of acerola crops is a potential alternative source of income in agricultural businesses. In Brazil, the commercial farming of acerola is quite recent. Climatic conditions. Acerola is a rustic plant. It can resist temperatures close to 0 degrees C, but it is well adapted to temperatures around 26 degrees C with rainfall between (1200 and 1600) mm per year. Fruit characteristics. Acerola fruit is drupaceous, whose form can vary from round to conic. When ripe, it can be red, purple or yellow. The fruit weight varies between (3 and 16) g. Maturation. Acerola fruit presents fast metabolic activity and its maturation occurs rapidly. When commercialised in ambient conditions, it requires fast transportation or the use of refrigerated containers to retard its respiration and metabolism partially. Production and productivity. Flowering and fruiting are typically in cycles associated with rain. Usually, they take place in 25-day cycles, up to 8 times per year. The plant can be propagated by cuttings, grafting or seedlings. Harvest. Fruits produced for markets needs to be harvested at its optimal maturation stage. For distant markets, they need to be packed in boxes and piled up in low layers; transportation should be done in refrigerated trucks in relatively high humid conditions. Biochemical constituents. Acerola is the most important natural source of vitamin C [(1000 to 4500) mg.100(-1) g of pulp], but it is also rich in pectin and pectolytic enzymes, carotenoids, plant fibre, vitamin B, thiamin, riboflavin, niacin, proteins and mineral salts. It has also shown active anti-fungal properties. Products and market. Acerola is used in the production of juice, soft drinks, gums and liqueurs. The USA and Europe are great potential markets. In Europe, acerola extracts are used to enrich pear or apple juices. In the USA, they are used in the pharmaceutical industry. Conclusions. The demand for acerola has increased significantly in recent years because of the relevance of vitamin C in human health, coupled with the use of ascorbic acid as an antioxidant in food and feed. Acerola fruit contains other significant components, which are likely to lead to a further increase in its production and trade all over the world.
Keywords: Brazil; Malpighia; fruits; proximate composition; uses; world markets